2023
DOI: 10.1038/s41467-023-38339-2
|View full text |Cite
|
Sign up to set email alerts
|

Switching imidazole reactivity by dynamic control of tautomer state in an allosteric foldamer

David P. Tilly,
Jean-Paul Heeb,
Simon J. Webb
et al.

Abstract: Molecular biology achieves control over complex reaction networks by means of molecular systems that translate a chemical input (such as ligand binding) into an orthogonal chemical output (such as acylation or phosphorylation). We present an artificial molecular translation device that converts a chemical input – the presence of chloride ions – into an unrelated chemical output: modulation of the reactivity of an imidazole moiety, both as a Brønsted base and as a nucleophile. The modulation of reactivity opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 52 publications
(36 reference statements)
0
11
0
Order By: Relevance
“…The ADAM foldamer occupies a unique space in the literature surrounding switchable foldamers. While there are examples of long-distance communication resulting in a change of chirality or tautomeric state, ,, the ADAM system demonstrates a novel form of long-distance communication through the NCN in which a stimulus input at the C-terminus results in reorganization of the N-terminus residues while maintaining the central core interaction in aqueous solution. In summary, the ability to harness biological mechanisms such as frustration in abiotic foldamers opens the possibility for increased complexity in responsive synthetic systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ADAM foldamer occupies a unique space in the literature surrounding switchable foldamers. While there are examples of long-distance communication resulting in a change of chirality or tautomeric state, ,, the ADAM system demonstrates a novel form of long-distance communication through the NCN in which a stimulus input at the C-terminus results in reorganization of the N-terminus residues while maintaining the central core interaction in aqueous solution. In summary, the ability to harness biological mechanisms such as frustration in abiotic foldamers opens the possibility for increased complexity in responsive synthetic systems.…”
Section: Discussionmentioning
confidence: 99%
“…Foldamers adopt well-defined structures that provide the features necessary to recapitulate such complex behavior observed in proteins, providing an approach for creating complex abiotic responsive systems. However, while dynamic foldamers that mimic allostery and stimulus response , have been reported, to the best of our knowledge, relief of frustration has not been used as a design element to induce long-distance structural reorganization in abiotic systems to date. Currently, the only reported example suggesting frustration as the driving force for structural rearrangement is a self-assembled [2]-catenane mutational study from our group; however, frustration was not intentionally incorporated in the system design as a mechanism for complex behavior.…”
Section: Introductionmentioning
confidence: 99%
“…In these systems, a positive or negative torsion of the chiral residue is favoured due to its intrinsic chirality, being difficult to reorient it in the opposite direction. To avoid this problem, the foldamer must be constituted mainly by achiral residues, 75–79 such as aminoisobutyric acid (Aib) (Fig. 1b), employed in the preparation of stimuli-responsive biotic foldamers where the two P (plus) and M (minus) twisted conformations are equally favoured.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that linear chains of ureas linked through ethylene bridges adopt a coherent and uniform hydrogen-bond directionality (Figure f) with a hydrogen bond-donating terminus and a hydrogen bond-accepting terminus. These molecules pack into cyclic supramolecular structures in the solid state that allow their terminal hydrogen-bonding capacity to be satisfied in an intermolecular manner . We speculated that linking the termini of an ethylene-bridged scaffold into a ring (Figure f, dashed line) could lead to cyclic, fully intramolecularly hydrogen-bonded structures, in which the cyclic hydrogen-bonding network may result in a new class of cyclochiral structure.…”
Section: Introductionmentioning
confidence: 99%